Viscous Elastic Asphalt Characteristics of Cariphalte Modification with Addition of Gilsonite Viewed from Phase Angle Value - Aszharri, Arief; Sari, Nadra Mutiara (Universitas Negeri Padang, 2024)
Performance Grade (PG) Bitumen is bitumen that is graded based on its performance at different temperatures. In the Superpave grading system, asphalt binders are classified according to their performance in extreme hot and cold temperatures and are referred to as performance grade (PG) asphalt. The main objective of assessing and selecting asphalt binder using the PG system is to ensure that the binder has properties suitable for the environmental conditions in the field. Cariphalte is a premium grade polymer modified bitumen used in road and airport construction and other similar applications. Cariphalte is a Styrene Butadine Styrene (SBS) modified bitumen. The SBS in Cariphalte ensures the formation of a 3-dimensional network in the bitumen thereby reducing the temperature susceptibility and increasing the stiffness modulus at high temperatures. Cariphalte is also resistant to oxidation, reducing deformation and slowing secondary solidification. To get an idea of the improvement in rheological properties due to the addition of gilsonite, tests were carried out on a mixture of cariphalte and gilsonite asphalt with 6 variations of gilsonite content. The tests carried out include basic rheological properties testing and mechanistic rheological properties testing. From this research, the test results showed that at the same temperature, asphalt with the addition of 0% gilsonite had the smallest phase angle (δ) compared to asphalt using the addition of gilsonite. This explains that the addition of gilsonite can increase the phase angle (δ) value of PG-76 asphalt, which makes the asphalt material have thicker characteristics.